DETERMINATION OF THE QUANTITY OF BIOLOGICALLY ACTIVE DYES IN LOCAL AMARANTH VARIETIES AND PROSPECTS FOR THEIR EFFECTIVE USE (Scientific journal of the Fergana State University, 2025)
This article discusses the prospects for the effective use of the amaranth plant, which is now recognized as a plant of the 21st century, and its cultivation, the uniqueness of the chemical composition of amaranth, the rich composition of biologically active compounds, its effective use in maintaining human health, the comprehensive use of local new varieties, highlights the problems of creating biologically active food supplements for the organization of functional nutrition and their implementation in practice. In order to create a natural energy drink for people engaged in active physical work, the above-ground parts of plants were used to determine the best local varieties of amaranth “O‘zbekiston-M”, “Andijon”, “Marhamat”, “Ulug‘nor”, taking extracts from leaves and petals, comparatively studied the amount of pigments in them: amaranth, chlorophylls, carotenoids. Based on the results obtained, a conclusion was made to use the varieties “Andijon”, “Marhamat” for these purposes.